2007
DOI: 10.1038/sj.onc.1210436
|View full text |Cite
|
Sign up to set email alerts
|

mir-29 regulates Mcl-1 protein expression and apoptosis

Abstract: Cellular expression of Mcl-1, an anti-apoptotic Bcl-2 family member, is tightly regulated. Recently, Bcl-2 expression was shown to be regulated by microRNAs, small endogenous RNA molecules that regulate protein expression through sequence-specific interaction with messenger RNA. By analogy, we reasoned that Mcl-1 expression may also be regulated by microRNAs. We chose human immortalized, but non-malignant, H69 cholangiocyte and malignant KMCH cholangiocarcinoma cell lines for these studies, because Mcl-1 is dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
608
1
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 759 publications
(642 citation statements)
references
References 31 publications
24
608
1
9
Order By: Relevance
“…Mott et al (2007) described that miR-29b is able to regulate Mcl1-1 protein and thus TRAIL-mediated cytotoxicity in cholangiocarcinoma cell lines. Corsten et al (2007) demonstrated that the combined effect of miR-21 antagonism and soluble TRAIL delivery in glioma cells leads to increase in caspase activity and cell death in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mott et al (2007) described that miR-29b is able to regulate Mcl1-1 protein and thus TRAIL-mediated cytotoxicity in cholangiocarcinoma cell lines. Corsten et al (2007) demonstrated that the combined effect of miR-21 antagonism and soluble TRAIL delivery in glioma cells leads to increase in caspase activity and cell death in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…miR-29b was previously correlated with good prognosis in patients with acute myeloid leukemia, and has a tumor suppressor function in leukemic blasts by targeting apoptosis, cell cycle and proliferation pathways (Garzon et al, 2008). Consistently, miR-29b regulates Mcl-1 and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-mediated apoptosis in cholangiocarcinoma cells, and controls Tcl-1 in chronic lymphatic leukemia cells (Pekarsky et al, 2006;Mott et al, 2007). The miR-29 family members also target DNMT3A and DNMT3B, and can thereby restore patterns of DNA methylation and expression of silenced tumor suppressor genes (Fabbri et al, 2007).…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, using the Src-specific small molecule inhibitors saracatinib and dasatinib, we identified miR-29b as an important mediator of the Src-ID1 pathway, controlling lung cancer cell invasion. Members of the miRNA-29 family (miR-29a, miR-29b and miR-29c) are known to be highly expressed in normal tissues and downregulated in different types of cancer, including neuroblastoma, sarcoma, glioma, high-risk chronic lymphatic leukemia, invasive breast cancer, cholangiocarcinoma and lung cancer (Calin et microRNA-29b in lung cancer SI Rothschild et al et al, 2006;Mott et al, 2007;Wu et al, 2009;Xu et al, 2009). The three miR-29 isoforms are arranged in two clusters: miR-29b1/miR-29a located on chromosome 7q32 and miR-29b2/miR-29c located on chromosome 1q32.…”
Section: Discussionmentioning
confidence: 99%
“…70,71 As for the pro-survival BCL-2 family members, BCL-2 and MCL-1 appear to be the prominent targets of miRNA-mediated regulation. Both are targeted by miR-29 and miR-153, [72][73][74] and BCL-2 expression is also regulated by miR-15, miR-16, 75 miR-195 76 and the p53-inducible miR-34. 77 BCL-XL expression appears to be controlled by miR-491.…”
Section: Mcl1mentioning
confidence: 99%